Resistance of Cancer Cells to CTL-Mediated Immunotherapy - Bonavida, Benjamin.; Bonavida, Benjamin.; Chouaib, Salem.; Chouaib, Salem. (Resistance to Targeted Anti-Cancer Therapeutics,, 2015)
This book, written by leading investigators, brings together the latest knowledge about key aspects of the most rapidly progressing fields of tumor escape and tumor resistance to CTL. Readers will benefit from a collection of outstanding surveys that cover some factors regulating resistance to CTL cytotoxicity, the influence of tumor microenvironment, and the resistance to death ligands, mediated apoptosis, and means to reverse resistance. This remarkable volume also emphasizes the future directions that may lead to the design of more innovative, refined,  and integrative immunotherapies to target tumor plasticity and heterogeneity, and help to overcome the inherent limitations of current treatments. By providing a broad scope of innovative concepts in the burgeoning field of cancer biology and immunotherapy, this volume will be of exceptional interest and a valuable reference for scientists, clinicians, health professionals, and biopharmaceutical companies working in the field of cancer immunotherapy.  .